(untitled) (Journal of Economic Research & Business Administration, 2016)
Timely, reliable and analytical information is necessary for adoption of operational and tactical decisions on management of the organizations and their structural divisions in the conditions of constantly changing en vironment and the developing competition of producers. As the basic data obtained as a result of supervision and primary reflection of the happen ing economic operations are information basis for management account ing, from their reliability, dates of receipt, processing and delivery to the interested users of the organization, correctness and validity of the made administrative decisions focused on the existing market situation depend. The function of the management representing an independent type of administrative activity is based on use of accounting information. Selection of accounting information has to be carried out according to object of ac tivity and nature of works which are caused by duty regulations. As a rule, duty regulations consist of sections: general provisions, duties, rights and responsibility. Strategic management accounting investigates all factors al lowing to make expenses effective and is real them to operate.